Enhancing Entrepreneurial Skills in Puncak Bogor Tourism Village - Anita Amalia (Jurnal PKM Manajemen Bisnis, 2022)
Beautiful nature is a bonus for an area, but it is more valuable or has added value if local people can maximize their potential. Therefore, improving the quality of human resources in the form of skills in producing natural products as souvenirs is a necessity. These skills are relevant to the regional theme, namely as a tourist destination. This service activity is carried out, aiming to share knowledge and provide training on processing agricultural products in tourist cities, so that they become regional specialties, and become a source of income. The activity method is training on making wedang in the Puncak Bogor area. The results of this activity, especially in the form of increased knowledge and skills in making wedang. Then increase public understanding about marketing products effectively, namely utilizing social media as information dissemination and image formation, so that production results are widely known by Indonesian people, especially visiting tourists.